The essence of malice - Weaver, Ashley (Weaver, Ashley. Amory Ames mystery., 2017)
When Milo Ames receives a troubling letter from his childhood nanny, Madame Nanette, he and his wife, Amory, travel to Paris where they are soon embroiled in a mystery surrounding the sudden death of a famous parfumier. Helios Belanger died shortly before the release of his newest, highly anticipated perfume and Madame Nanette is convinced her employer<U+2019>s death was not due to natural causes. As Amory and Milo investigate the motives of industry rivals and the Belanger heirs, secrets unfold and danger surrounds them. Can the pair uncover the essence of the matter and catch a killer before the scent goes cold?